Evaluation of Pharmacodynamics Properties of "Thalankai Ennai" for "Alal Keel Vaayu" (Akv) - Printhaban, K.; Lakshana, B.; Sathiyaseelan, V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2017)
Siddhas are the pioneers who used "Tamil" effectively which is the communication language of "Dravidas" and one of the special aspects of Hindu civilization as well. Siddha medicine is evolved from the experience, the inventions, discoveries and findings of the great siddhas. In Siddha medicine, herbs or plant parts, animal products, minerals and metals are used to prepare medicines. Generally, "Keel Vaayu" is a disease mainly related with joints. It arises in body due to the increase or decrease in the ordinary equilibrium of "Uyir Thaathukal". It causes pain, loss of function, swelling, redness, crepitus and leads to many discomforts and deformities. The Sleshmika Kapha (fluid) will get dry and causes friction and makes crepitus sound and this condition is called as "Alal Keel Vaayu." For this "Alal Keel Vaayu", traditional Siddha doctors use oil application, massage (Thokkanam), poultice (Pathu), etc. According to that, our research objective is to find out the herbs, animal products, minerals and metals used in the "Thalankai oil" which is described in "Irupalai Settiyar Vaithiya Vilakam" and to identify their taste (Suvai), potency (Thanmai), postdigestive stage (Pirivu) and actions relevant to "Alal Keel Vaayu". Altogether, 21 ingredients are added to prepare this oil. 90.47% are plant material, 4.76% are animal products, 4.76% are minerals and 23.07% - sweet, 3.84% - salt, 54.54 - hot potency, 45.45% - cold potency. In post digestive stage, 54.54% are pungent, 45.45% are sweet. When we look into the actions, 12.02% - diuretic, 4.04% - antispasmodic, 7.07% - anti-inflammatory, 2.02% - emollient, 3.03% - laxative, 1.01% - deobstruent. Further, Gingelly oil, a base oil taken from gingelly seeds is added which is sweet in taste, has hot potency (Thanmai), sweet post digestive stage (Pirivu) and cooling action along with "Thalankai extract" which also has cooling action. These give strength to joints and increase "Sleshmika Kapha" in joints. So, the research reveals that the organoleptic characters of ingredients which will cure "Alal Keel Vaayu" and removing the friction between the joints are found in the in this oil. So, this is a best medicine for "Alal Keel Vaayu" indeed.
Keywords: Pharmacodynamics; Thalankai Ennai; Alal Keel Vaayu